Prevalence of microorganisms of hygienic interest in an organized abattoir in Mumbai, India - Bhandare, Sudhakar Ganpati; Paturkar, Ashish M; Waskar, Vikas S; Zende, Ravindra J (The Journal of Infection in Developing Countries, 2010)
Background: The magnitude of food-borne illnesses in India is unknown because of lack of surveillance networks. Monitoring the prevalence of food-borne pathogens and indicators of contamination in primary production at abattoirs is imperative for creating a data bank and for effective control of such pathogens before they enter the food chain. Methodology: Microorganisms of hygienic interest were screened for their prevalence at Deonar Abattoir, Mumbai. Swab samples from 96 sheep/goat carcass sites were collected and analyzed for Staphylococcus spp., Bacillaceae, Clostridiaceae and Enterobacteriaceae. Results: Average Staphylococcus aureus and Staphylococcus epidermidis counts were 3.15 ± 0.18 and 3.46 ± 0.17 log10 CFU/cm2, respectively. Bacillus cereus, Bacillus subtilis and Clostridium spp. counts were 3.10 ± 0.08, 3.41 ± 0.19 and 0.76 ± 0.06 log10 CFU/cm2, respectively. The Escherichia coli count was 3.54 ± 0.06 and the Klebsiella aerogenes count was 3.22 ± 0.22 log10 CFU/cm2. Counts for Proteus vulgaris and Proteus mirabilis were 3.44 ± 0.14 log10 CFU/cm2 and 3.71 ± 0.12 log10 CFU/cm2, respectively. S. epidermidis had the highest percentage prevalence at (41.6%), followed by K. aerogenes (31.9%), B. subtilis (28.2%) and P. vulgaris (23.6%). Salmonella spp. were not isolated. Conclusions: The data demonstrate high prevalence and diversity of micro flora on carcasses in the primary Indian production facility, which might be attributed to either human handling or improper dressing especially during evisceration process. Appropriate training for personal and production hygiene is essential for workers in Indian meat production facilities.